Factors and Predictions for Cadmium Transfer from Soils into Tomato Plants. Issue 13 (5th August 2016) - Qu, Ronghui; Zeng, Saiqi; Ding, Qiong; Liang, Zhenfei; Wei, Dongpu; Li, Jumei; Ma, Yibing
ABSTRACT: Soil-plant transfer models are needed to predict levels of cadmium (Cd) in vegetables when evaluating the food chain risks of Cd contamination in agricultural soils. In the present study, the transfer of Cd from a wide range of soils into tomato plants was investigated in order to identify the major factors and to develop predictive models. It was found that soil pH was the main factor controlling Cd uptake and lower pH was more favorable for Cd bioaccumulation. Furthermore, the hydrogen ion activity, other than pH, was correlated linearly with the ratio of plant Cd to soil Cd. Combining soil Cd, and the interaction between soil Cd and hydrogen ion activity greatly improved the model to predict the transfer of Cd from soil to plant. Compared with the previous log transformation model, the predicted model improved the regression coefficient from 0.799 to 0.973 and has important significance in practice.